Corrosion inhibition properties of graphene and reduced graphene oxide on aluminum surface: a comparative analysis from experimental and theoretical studies - Balaram Polai; Aiswarya Samal; Satyajit Ratha; Debashish Das; Saroj Kumar Nayak (Nano Express)
The corrosion protection of metals has long been considered a key challenge for researchers at both industrial and academic levels. While numerous state-of-the-art corrosion protection techniques exist for metals like copper, iron, steel, and zinc, there are few reports on preventing aluminum (Al) from corrosion. This study introduces an innovative method for protecting aluminum from corrosion through the anodic electrochemical deposition of reduced graphene oxide (rGO) coatings. The anti-corrosion performance of rGO-coated aluminum (Al/rGO) substrates was examined in 1.0 M hydrochloric acid (HCl) and 1.0 M sodium chloride (NaCl) solutions, utilizing electrochemical techniques. The in situ reduction of the graphene oxide (GO) coatings has shown significantly enhanced corrosion protection for aluminum compared to uncoated surfaces. The experimental findings demonstrate that rGO coatings protect against corrosive substances due to their hydrophobicity, diffusion site blockage, and tortuous diffusion path mechanisms on the aluminum surface. Additionally, to gain further insight into this study, with the help of density functional theory (DFT), analysis has revealed the weaker binding of corrosive species, such as NaCl−, HCl molecules, and Cl ^− ions with graphene- as well as rGO-coated Al surfaces (Al/Gr and Al/rGO) in comparison to their stronger binding with the uncoated Al surface. The diffusion energy barrier study has shown that the corrosive species must go through a high diffusion energy barrier to react with Al/Gr and Al/rGO surfaces compared to the bare Al surface. The combined experimental and theoretical studies found that rGO strongly binds with the Al surface, thus providing favorable corrosion protection for the bare Al surface.